Baicalein alleviates tubular-interstitial nephritis in vivo and in vitro by down-regulating NF-κB and MAPK pathways - Chen,Yan (2018)
Tubular-interstitial nephritis (TIN) is characterized by tubular cell damage and inflammatory lesions of kidneys. Baicalein (BAI) is a flavonoid compound found in the roots of Scutellaria baicalensis Georgi. The present study was undertaken to explore the anti-inflammatory and anti-oxidative effects of BAI on TIN patients and a lipopolysaccharide (LPS)-induced TIN cell model. The expression levels of interleukin-6 (IL-6), IL-10, and tumor necrosis factor α in serum samples of TIN patients and culture supernatants of renal proximal tubular epithelial cells (RPTECs) were evaluated using enzyme-linked immunosorbent assay. Creatinine clearance was calculated using the Cockcroft-Gault equation. Activities of malondialdehyde, superoxide dismutase, and glutathione peroxidase were also determined. Viability and apoptosis of RPTECs were measured using MTT assay and Guava Nexin assay, respectively. qRT-PCR was performed to determine the expressions of Bax, Bcl-2, nuclear factor kappa B (IκBα), and p65. Protein levels of Bax, Bcl-2, IκBα, p65, c-Jun N-terminal kinase, extracellular regulated protein kinases, and p38 were analyzed using western blotting. We found that BAI reduced inflammation and oxidative stress in vivo and in vitro. Moreover, BAI alleviated the LPS-induced RPTECs viability inhibition and apoptosis enhancement, as well as nuclear factor kappa B (NF-κB), and mitogen-activated protein kinase (MAPK) activation. Phorbol ester, an activator of NF-κB, attenuated the effects of BAI on LPS-induced inflammatory cytokine expressions in RPTECs. In conclusion, BAI had anti-inflammatory and anti-oxidative effects on TIN patients and LPS-induced RPTECs by down-regulating NF-κB and MAPK pathways.